EVALUATING LOCAL GOVERNANCE STRATEGIES IN STUNTING PREVENTION: A CASE STUDY OF THE STUNTING CASE AUDIT PROGRAM IN SEYEGAN SUBDISTRICT, SLEMAN REGENCY - Ayu, Fhanisa; Faidati, Nur (Journal of Social Politics and Governance (JSPG), 2025)
This study analyzes the effectiveness of the Stunting Case Audit (SCA) program in Kapanewon Seyegan, Sleman Regency. The program has shown measurable success in reducing stunting prevalence from 8.1% (2021) to 6.9% (2023). A qualitative approach was employed, using data collection methods such as observation, interviews, and documentation. The study focuses on four effectiveness indicators: target accuracy, program socialization, goal achievement, and monitoring system. The results indicate that the SCA program effectively identified high- risk stunting groups, despite limitations related to sampling and participation. Socialization was considered effective, with positive community responses and concrete follow-up interventions. The identification of stunting determinants allowed for more targeted actions, while routine monitoring by health center staff and the Family Assistance Team (TPK) supported program success. Continuous evaluation is essential to ensure the sustainability and broader impact of this regional intervention.